A comparative study of stabilising effect and antioxidant activity of different antioxidants on levodopa-loaded liposomes. (19th May 2018) - García Esteban, Elena; Cózar-Bernal, María José; Rabasco Álvarez, Antonio M.; González-Rodríguez, María Luisa
Abstract: The aim of this study was to evaluate the stability of levodopa liposomes co-loaded with three different antioxidants (curcumin, ascorbic acid, and superoxide dismutase (SOD)). For this purpose, multilamellar liposomes were prepared. Curcumin was added into the lipid bilayer while ascorbic acid and SOD were placed into the aqueous phase. The influence of preparation technique and surface charge were also investigated. Vesicles were characterised and free radical scavenging potential was determined. From stability study, ascorbic acid showed better stabilising effect. These co-loaded liposomes also exhibited potential radical scavenging activity where ascorbic acid played a key role. From the study of different preparation techniques and charge, we concluded that cationic liposomes made by Thin Layer Evaporation following extrusion offered the best physicochemical and stability properties. A dual mechanism of these liposomes implies the chemical stabilisation of levodopa (dose reduction) and the antioxidant effect, with a preventive effect on Parkinson's disease.